Review Paper on Spine Biomechanics: An Overview: Exploring the Dynamics and Complexity of Spine Biomechanics (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This article reviews the many theoretical and practical simulation research reports on the spine biomechanics with the help of musculoskeletal system. Cervical spine is the frequent site for injury in the column of spinal cord. It is difficult to co-relate the theoretical concepts of spine biomechanics and empirical data due to their dynamism and complexity of their mechanical response. We can better explain the biomechanics of spine with the help of mechanics or structural system which are mainly compressive or tensile in nature. FE analysis is applied for the simulation of different types of clinically relevant situations. With the help of FE model, researcher can make a better decision before applying more extensive tests which are costly. And by this we can go for the simulation of 2D as well as 3D analysis.